2017
DOI: 10.1103/physrevfluids.2.084604
|View full text |Cite
|
Sign up to set email alerts
|

Scalar statistics in variable property turbulent channel flows

Abstract: Direct numerical simulation of fully developed, internally heated channel flows with isothermal walls is performed using the low-Mach-number approximation of Navier-Stokes equation to investigate the influence of temperature-dependent properties on turbulent scalar statistics. Different constitutive relations for density ρ, viscosity μ, and thermal conductivity λ as a function of temperature are prescribed in order to characterize the turbulent scalar statistics. It is shown that the dominant effect caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…This leads to a strong temperature-velocity coupling, notwithstanding the compressibility effects due to velocity being negligible. Analyses of strongly anisothermal channel flows have been carried out using large-eddy simulations [11,34,35,54,55,56,53,47,48,63,8] and direct numerical simulations (DNS) [44,41,62,3,4,17,19,21]. As the velocity of the fluid is low compared to the speed of sound, the low Mach number equations may be used to relieve the numerical constraints related to acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a strong temperature-velocity coupling, notwithstanding the compressibility effects due to velocity being negligible. Analyses of strongly anisothermal channel flows have been carried out using large-eddy simulations [11,34,35,54,55,56,53,47,48,63,8] and direct numerical simulations (DNS) [44,41,62,3,4,17,19,21]. As the velocity of the fluid is low compared to the speed of sound, the low Mach number equations may be used to relieve the numerical constraints related to acoustic waves.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was found that the viscous shear stress is a universal function in the inner layer when expressed in the semi-local parameter,, where h is half-channel height. It was later shown in Patel, Boersma & Pecnik (2017) that the statistics of a scaler (such as temperature) can also be scaled using the semi-local Reynolds number and a semi-local defined as . The above idea was further used in Pecnik & Patel (2017) to derive a so-called semi-local scaled transport equation for turbulence kinetic energy, in which the viscous terms are scaled with and the turbulence production is governed by the gradient of the van Driest velocity.…”
Section: Introductionmentioning
confidence: 74%
“…1995) and to a lesser extent the effect of variable viscosity as well (Trettel & Larsson 2016; Patel et al. 2017) under conditions when buoyancy is not significant or is omitted. A common goal of these studies is to find a suitable normalisation so that the non-dimensionalised turbulence is unchanged from that of the equivalent constant-property flow.…”
Section: Discussionmentioning
confidence: 99%
“…In equations ( 6) and ( 7), the Reynolds shear stress and turbulent heat flux were modelled using the Boussinesq approximation and the gradient diffusion hypothesis, respectively. In [24], it was seen that the turbulent Prandtl number, P r t , varies around unity for the low-Mach number cases, implying that there is a strong analogy between the momentum and scalar transport. Therefore, we have approximated P r t = 1 also for the high-Mach number case.…”
Section: Fully Developed Channel Flowmentioning
confidence: 98%